Draft Annual Plan 1990-91 Government of Sikkim - Planning Commission (Planning Commission, 1990)
The broad, strategy to be followed as far as Sikkim is concerned during the Eighth Five Year Plan has been outlined in the main document containing the proposals for the State during the period 1990-95. This interlaid indicates that the State would be aiming at a growth rate of approximately 10% per annum, by stepping up the quantum investment, improvement in the efficiency with which capital is being utilised, reduction in the capital output ratio, and an improvement in the Science & Technology content in the development plan.
Planning and Development Department, Government of Sikkim